Molecular Detection of Nuc and Hib Genes of Staphylococcus Aureus Isolated from Burn Patients in Baghdad Province - Durib, Ali Kareem (Indonesian Journal on Health Science and Medicine, 2025)
The current study was conducted to identify pathogenic Staph. Aureus that coexist with Burn Patients and characterize these bacteria based on some virulence genes using bacteriological and molecular techniques such as PCR. The study was carried out on 66 samples isolated from Burn patients in different hospitals in Iraq, Baghdad Province. These samples were cultivated on traditional and specific media agars for the identification of certain pathogenic bacteria. The results the results show that out 66 wound swabs, 55 (88.3%) of them growth Staph. aureus. The highest susceptible antibiotics against Staph. Aureus in this study were Imipenem (IPM), Cefepime (CPM), Ceftriaxone (CRO), and Cefotaxime (CTX) as (76%, 66%, 63%, and 61, respectively), while the highest resistant antibiotics were Cefixime (CFM), Vancomycin (VAN), and Amikacin (AK) as (84%, 75%, and 50%, respectively). In the current study, the molecular detection showed that 55(83.3%) of staph aureu were positive for Nuc gene. In the current study demonstrate that the S. aureus is adequate medium for growth of and production of enterotoxins. The study findings reveal a diverse community of bacterial species present in samples isolated from patients with Burn infections with high virulence, detected by the presence of virulence genes. Highlights:  High Prevalence of Staph. aureus: 88.3% of wound swabs from burn patients tested positive for Staph. aureus, indicating a significant presence in burn infections. Antibiotic Resistance Patterns: The bacteria showed high resistance to Cefixime (84%) and Vancomycin (75%), raising concerns about treatment effectiveness. Virulence Gene Detection: 83.3% of Staph. aureus isolates carried the Nuc gene, highlighting their potential for high virulence and enterotoxin production. Keywords: Staph. aureus, Burn Infections, Antibiotic Resistance, Virulence Genes, PCR Detection